Angled Growth of the Dental Lamina Is Accompanied by Asymmetrical Expression of the WNT Pathway Receptor Frizzled 6 - Putnová, Iveta; Dosedělová, Hana; Bryja, Vitezslav; Landová, Marie; Buchtová, Marcela; Štembírek, Jan (Frontiers in Physiology, 2017)
Frizzled 6 (FZD6) belongs to a family of proteins that serve as receptors in the WNT signalling pathway. FZD6 plays an important role in the establishment of planar cell polarity in many embryonic processes such as convergent extension during gastrulation, neural tube closure or hair patterning. Based on its role during hair development, we hypothesized that FZD6 may have similar expression pattern and function in the dental lamina, which is also a distinct epithelial protrusion growing characteristically angled into the mesenchyme. Diphyodont minipig was selected as a model species because its dentition closely resemble human ones with successional generation of teeth initiated from the dental lamina. We revealed asymmetrical expression of FZD6 in the dental lamina of early as well as late stages during its regression with stronger expression located on the labial side of the dental lamina. During lamina regression, FZD6-positive cells were found in its superficial part and the signal coincided with the upregulation of molecules involved in epithelial-mesenchymal transition and increased migratory potential of epithelial cells. FZD6-expression was also turned on during differentiation of cells producing hard tissues, in which mature odontoblasts, ameloblasts or surrounding osteoblasts were FZD6-positive. On the other hand, the tip of successional lamina and its lingual part, in which progenitor cells are located, exhibited FZD6-negativity. In conclusion, asymmetrical expression of FZD6 correlates with the growth directionality and side-specific morphological differences in the dental lamina of diphyodont species. Based on observed expression pattern, we propose that the dental lamina is other epithelial tissue, where planar cell polarity signalling is involved during its asymmetrical growth.